Association of serum levels of C-reactive protein with CRP-717 T/C polymorphism and viremia in HCV and HBV carriers - Tuane Carolina Ferreira Moura; Ednelza da Silva Graça Amoras; Maria Alice Freitas Queiroz; Simone Regina Souza da Silva Conde; Alan Barroso Araújo Grisólia; Ricardo Ishak; Antonio Carlos Rosário Vallinoto (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: The present study investigated the association of the rs2794521 polymorphism in the CRP gene in individuals with chronic hepatitis B and C, correlating it with markers of hepatic inflammation, fibrosis scores, viral load, and plasma protein levels. METHODS: The study analyzed 185 blood samples obtained from patients with hepatitis B (n=74) and hepatitis C (n=111) and 300 samples from healthy donors. Genotyping was performed by real-time polymerase chain reaction, and protein levels were quantified using the automated immunoturbidimetric method. RESULTS: The TT genotype was the most frequent in all studied groups and was associated with higher plasma levels of the protein but not with the progression of liver disease. Low levels of C-reactive protein were associated with increased viremia and scores indicative of severe fibrosis and cirrhosis. CONCLUSIONS: The present results demonstrated a close relationship between the ability of the virus to replicate and cause liver damage and low serum concentrations of C-reactive protein. Future research may determine if these results can be interpreted as a possible form of escape for the virus by decreasing its action as an opsonin and decreasing phagocytosis, which are functions of C-reactive protein in the immune response.